Plasma membrane dynamics and tetrameric organisation of ABCG2 transporters in mammalian cells revealed by single particle imaging techniques - Wong, Kelvin; Briddon, Stephen J.; Holliday, Nicholas D.; Kerr, Ian D. (Elsevier, 2016)
ABCG2 is one of three human ATP binding cassette (ABC) transporters involved in the export from cells of a chemically and structurally diverse range of compounds. This multidrug efflux capability, together with a broad tissue distribution in the body, means that ABCG2 exerts a range of effects on normal physiology such as kidney urate transport, as well as contributing towards the pharmacokinetic profiles of many exogenous drugs. The primary sequence of ABCG2 contains only half the number of domains required for a functioning ABC transporter and so it must oligomerise in order to function, yet its oligomeric state in intact cell membranes remains uncharacterized. We have analysed ABCG2 in living cell membranes using a combination of fluorescence correlation spectroscopy, photon counting histogram analysis, and stepwise photobleaching to demonstrate a predominantly tetrameric structure for ABCG2 in the presence or absence of transport substrates. These results provide the essential basis for exploring pharmacological manipulation of oligomeric state as a strategy to modulate ABCG2 activity in future selective therapeutics.